Exploring instructional leadership of private preschool principals in advancing the national education blueprint implementation - Hoo, Wong Chee; Manogaran, Sharmila Devi; Annamalah, Sanmugam; Ahmed, Selim; Sentosa, Ilham (International Journal of Innovative Research and Scientific Studies, 2025)
This research evaluates private preschool principals' leadership effectiveness within the National Education Blueprint (2013-2025), assessing instructional competence, CPD influence, and barriers to knowledge application. Aimed at understanding instructional leadership in private preschools, it seeks to identify and address performance improvement obstacles. The study employed purposive sampling, by obtaining consent from 10 preschool principals. Participants were granted unrestricted access and complete autonomy in various aspects of school administration. This includes overseeing student-teacher interactions, curriculum improvement, and nurturing relationships with families. Documentation and a checklist were provided to evaluate participants' initial understanding of the research process. The findings highlight areas for enhancing principals' competencies, promoting positive perceptions of CPD, and addressing obstacles related to its implementation and acquisition. Challenges include parental pressures impacting school visions and time constraints due to teachers' confidence issues. Principals prioritize practical experiences over academic credentials and express interest in improving Early Childhood Care and Education (ECCE). Obstacles to CPD acquisition include time limitations, financial constraints, and implementation difficulties. This study provides valuable insights into the roles of private preschool principals in enhancing school performance and children's achievements. It underscores the connection between instructional leadership, school efficacy, and children's overall success. The findings have significant implications for instructional leadership and professional development in private preschool settings, guiding the enhancement of training content and methodologies for principals and educators.